Knowledge management and innovation of a company with organic banana export potential - Román Lima, María del Carmen; Cosio Borda, Ricardo Fernando; Ramírez-Briones, Lorena; Cajavilca-Gonzáles, Berenice; Noriega-Monar, Gloria; Cordova Godos, Rosita Elena (LACCEI, 2025)
This research, aligned with ODS N° 8: Decent work and economic growth, had the general objective of determining the relationship between knowledge management and innovation in a company with organic banana export potential in Sullana, Peru, during the period 2024 - II. The specific objectives focused on identifying the relationship between knowledge management and the product/service, process, commercial and organizational dimensions of innovation. This is an applied research with a quantitative approach, correlational type and with a non-experimental and cross-sectional design. The study population was 70 employees of the company, from which a census sample of 40 was selected. The results indicated that there is no significant relationship between knowledge management and innovation in the company studied. Although a high level of knowledge management is perceived, it does not translate into a greater capacity for innovation. It is concluded that knowledge management in the company is not yet applied in a strategic way to drive innovation.